2007
DOI: 10.1086/522293
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Evolutionary Age and Metallicity in the Formation of Classical Be Circumstellar Disks. II. Assessing the Evolutionary Nature of Candidate Disk Systems

Abstract: We present the first detailed imaging polarization observations of six SMC and six LMC clusters, known to have large populations of B-type stars that exhibit excess H emission from 2-CD photometric studies, to constrain the evolutionary status of these stars and hence better establish links between the onset of disk formation in classical Be stars and cluster age and/or metallicity. We parameterize and remove the interstellar polarization (ISP) associated with each line of sight, thereby isolating the presence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 61 publications
3
42
0
Order By: Relevance
“…Thereafter, there is an increase during the evolution, and another decrease after 50-60 Myr (log (age) = 7.7-7.8). Figures 13 and 14 indicate that some Be stars could be born as Be stars (Wisniewski et al 2007b), while others only happen to have Be characteristics during the evolution as mentioned by Fabregat & Torrejón (2000). The first decrease, if real (the differences between the studies being compared are large), could be caused by Be stars reaching the terminal-age main-sequence or by an evolutionary change in the angular velocities so that not every initial Be star can sustain a high enough surface rotation rate to remain a Be star throughout its entire main-sequence life (Martayan et al 2007b).…”
Section: The Be Phenomenon: Smc Vs Galaxymentioning
confidence: 68%
See 2 more Smart Citations
“…Thereafter, there is an increase during the evolution, and another decrease after 50-60 Myr (log (age) = 7.7-7.8). Figures 13 and 14 indicate that some Be stars could be born as Be stars (Wisniewski et al 2007b), while others only happen to have Be characteristics during the evolution as mentioned by Fabregat & Torrejón (2000). The first decrease, if real (the differences between the studies being compared are large), could be caused by Be stars reaching the terminal-age main-sequence or by an evolutionary change in the angular velocities so that not every initial Be star can sustain a high enough surface rotation rate to remain a Be star throughout its entire main-sequence life (Martayan et al 2007b).…”
Section: The Be Phenomenon: Smc Vs Galaxymentioning
confidence: 68%
“…Of the 7 remaining emission-line stars, 4 (WBBe5, WBBe10, WBBe17, WBBe20) are in common to both studies. One star (WBBe7), for which Wisniewski et al (2007b) did not publish polarimetry, is found not to have emission. The two others (WBBe6 and WBBe21) are faint and have a too low S/N to provide a reliable conclusion about the presence of emission in their spectra.…”
Section: A2 Bruck 60 (Ogle-smc72)mentioning
confidence: 99%
See 1 more Smart Citation
“…and larger statistical ensembles (Coyne & Kruszewski 1969;McLean & Brown 1978;Poeckert et al 1979;Wisniewski et al 2007b). Electron scattering modified by pre-or postscattering absorption by hydrogen atoms in the disk produces the characteristic wavelength-dependent polarization signature of Be stars (Wood et al 1996a(Wood et al , 1996b.…”
Section: Disk-loss and Disk-renewal Phases In Classical Be Stars I mentioning
confidence: 99%
“…It inherently assumes the existence of uniform interstellar medium conditions in the vicinity of the target and also assumes that the field stars themselves are devoid of any intrinsic polarization component. While the technique can be highly successful when used to analyze the ISP properties of open clusters, where one can assume all members are located at the same distance and there are sufficient numbers of stars to lessen the effects of small intrinsic polarization components in the field stars by brute force averaging of a large number of stars (see, e.g., Wisniewski et al 2007b), the application of the technique to isolated stars often yields imprecise ISP estimates (see McLean & Clarke 1979;Bjorkman et al 1998;and Wisniewski et al 2006).…”
Section: Field Star Techniquementioning
confidence: 99%